Concurrent analysis: a pragmatic justification - Snowden, Austyn (Nursing philosophy, 2012)
Concurrent analysis (CA) is a process of synthesizing conceptually equivalent data for the purpose of producing a coherent and predictive model in social science. The process of CA is detailed. In short, CA uses Thagard's concept of coherence as a method of explicating links between mental representations. The product is a wide analysis of all pertinent data. This paper provides a philosophical justification for the need and function of CA. The paper is divided into three sections. The first section reviews some problems with the metasynthetic literature. The purpose of this is that CA can be initially understood as a branch of this type of synthesis. The second section links Risjord's post-paradigmatic position to Rorty's version of pragmatism in order to show the importance of the concept of coherence to these views. The reason for linking these issues is that CA is grounded in rejection of ontological priority. Instead it prioritises a pragmatic conception of coherence. The final section details the mechanics of CA. Concurrent analysis is presented as the most coherent method of synthesizing certain types of narrative evidence if pragmatism is prioritized over ontology. Examples are given from published studies using CA to illustrate the detail of the analysis and the practical value of the product. The examples show that CA appears useful under certain circumstances. These circumstances will be specified, and strengths and weaknesses of the method will be discussed.